ANALISIS RISIKO SAHAM PERUSAHAAN REAL ESTATE DAN PROPERTY DI BURSA EFEK INDONESIA - Indri Hafsari Gultom; Khaira Amalia Fachrudin (Universitas Sumatera Utara, 2013)
Abstract This research aims to determine and analyze the differences in systematic risk and unsystematic risk between the real estate and property sub-sector and building construction sub-sector ini The Indonesian Stock Exchange. This research is comparative research. Sampling techique using saturated samples with a total samples 51 companies, comprising 44 companies real estate and property sub-sector and 7 companies building construction sub-sector. This research uses secondary data. The analysis method used is descriptive analyze and statistical method, independent sample t-test was used to analyze the differences in systematic risk and unsystematic risk between the real estate and property sub-sector and building construction. The results of this research indicate that there was no difference in systematic risk and unsystematic risk between the real estate and property sub-sector and building construction sub​​-sector with alpha 0.05. The implication of this research are investors can invest on both sub-sectors because there is no difference in systematic risk and unsystematic risk between of real estate and property sub-sectors and building construction sub-sectors. Keywords: systematic risk, unsystematic risk, real estate and property sub-sector, building construction sub-sector.